Aspek hukum keperdataan terhadap pemenuhan hak restitusi dalam perkara tindak pidana - Wardatul Fitri; FX Djoko Priyono; Bambang Eko Turisno (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to analyze criminal law enforcement that has occurred and has fulfilled the community's sense of justice (victims of criminal acts and the contribution of civil law science in the practice of criminal law enforcement). The research was conducted qualitatively by using a statutory approach and normative juridical research. The results of the research show firstly that the practice of enforcing criminal law based on Law Number 8 of 1981 concerning the Criminal Procedure Code as a formal law still emphasizes "retributive" forms of justice. The form of compensation (restitution), the recovery of losses suffered by the victims, has not been accommodated properly, so that the community, especially victims of crime, feels that they have not fulfilled their sense of justice. Second, the contribution and role of civil law in criminal law enforcement are very relevant. One of them is by filing a claim for payment of restitution, including by filing a civil suit against the convict's family for the payment of restitution. so that there will be legal certainty for victims of criminal acts about the responsibility of the perpetrators in relation to restitution for violations of the rights of victims of criminal acts.